Answer:
their marriage and 2 years before
Answer:
AB-C^2 = 3x^3 + x^2 + 9
Step-by-step explanation:
Hi
AB = (x^2)*(3x+2)= 3x^3 + 2x^2
C^2= (x-3)^2 = x^2 - 9
So
AB-C^2 = 3x^3 + 2x^2 - x^2 + 9 = 3x^3 + x^2 + 9
Answer:
-6.95 x 10^10
Step-by-step explanation:
Answer:
B & C
Step-by-step explanation:
Use the Pythagorean Theorem: a^2 + b^2 = c^2
A) 18^2 + 24^2 = 2,088 | 42^2 = 1,764 [NOT A]
B) 33^2 +56^2 = 4,225 | 65^2 = 4,225 [B IS CORRECT]
C) 19^2 + 180^2 = (32,761) = 181^2 = (32,761) [C IS CORRECT]
D) 3^2 + 4^2 = 25 | 7^2 = 49 [NOT D]
I hope this helped you ! In return, please deem this the most brainliest answer.
Answer: he will have $12720 after 15 years
Step-by-step explanation:
We would apply the formula for determining compound interest which is expressed as
A = P(1 + r/n)^nt
Where
A = total amount in the account at the end of t years
r represents the interest rate.
n represents the periodic interval at which it was compounded.
P represents the principal or initial amount deposited
From the information given,
P = $8000
r = 3.1% = 3.1/100 = 0.031
n = 12 because it was compounded 12 times in a year.
t = 15 years
Therefore,
A = 8000(1 + 0.031/12)^12 × 15
A = 8000(1 + 0.00258)^180
A = 8000(1.00258)^180
A = $12720